Environmental and socio-economic impacts of new plant breeding technologies: A case study of root chicory for inulin production - Hingsamer, Maria; Kulmer, Veronika; de Roode, Matthew; Kernitzkyi, Michael (Frontiers in Genome Editing, 2022)
In Europe, root chicory and other plants are cultivated for their prebiotic food fiber, inulin, which boosts the growth of beneficial gut bacteria and stimulates the human immune system. CHIC, a H2020 project, develops new chicory variants which produce more and reported to be healthier inulin as well as medicinal terpenes. This paper presents an environmental and socio-economic assessment of the whole value chain of the new chicory variants and their derived products using a case study based in the Netherlands. Two scenarios based on new chicory variants using new plant breeding technologies (NPBT) are analyzed and impacts thereof are compared to the reference scenario; the current commercial inulin process from conventional chicory. Both scenarios show higher inulin content, but the inulin adsorption process differs. While one aims to optimize inulin yield, the other one explores the potential of a multipurpose use, yielding inulin and health beneficial terpenes. Methodologically, we employ multi-regional input-output (MRIO) analysis to estimate additional economic benefits, added value and job creation, while by means of life cycle assessment (LCA) effects on greenhouse gas (GHG) emissions and primary energy demand are derived. Both methods, MRIO and LCA, are well suited to analyze the raised issues and draw on the same data. Generally, the results highlight the importance of inulin production at a national and EU-level in the reference scenario. In case of the two scenarios, we find that the related socio-economic impacts are much higher than in the reference scenario and thus highlight their ability to boost economic activity and increase competiveness of the EU, i.e. over 80% of the generated value added stays in the EU. In terms of environmental impacts, the two scenarios show lower GHG emissions and primary energy demand due to the higher efficiencies of the process in the scenarios compared to the reference inulin process. Additionally, regarding the goal of climate neutral production, we find that the majority of GHG emissions stem from the electricity mix and natural gas demand. Replacing these sources of energy with more renewable ones will contribute to this goal.